Research of dynamic characteristics of technological systems in processing control in elastoplastic deformation conditions of flexible shafts - Taranenko, Viktor (Journal of Production Engineering, 1993)
In situations where comprehensive and precise information about the control object is lacking, the idealization of the dynamic properties of control system elements can lead to significant discrepancies between calculated and actual characteristics. The selected parameters and settings of controllers in the design phase may not guarantee the desired control quality or system stability. Furthermore, systems under consideration exhibit wide parameter variations. In technological systems involving cutting processes, parameters can vary significantly during the processing cycle of a single part. These challenges complicate the task of ensuring control system stability, necessitating a meticulous approach to structure selection and corrective device synthesis. Developing a mathematical model of the control object that accurately represents its dynamics is a crucial prerequisite for a systematic approach to stability analysis, guided by specified control quality criteria during transient phases. In such systems, control quality indicators for output coordinates, particularly elastic deformations within the dynamic technological system, directly reflect shape errors in the part resulting from rapidly changing disturbances like alterations in processing allowances and variations in the physical and mechanical properties of the processed material.